The Economic Assessment of Research and Development - Libik, George (Management Science, 1969)
This is an informative paper about the position and situation of R & D (applied) in Eastern and Western Europe. Based on different sources the study also shows a part of the growing differences (different opinions) about importance, understanding and methods to evaluate the efficiency of R & D. It also discusses the “double concept” of R & D efficiency, namely as a summary of successful research results and product application with marketing effect.